Dr. Ahn Dong Hyun — Deep Plane Facelift — Seoul - Hyun, Ahn Dong (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Ahn Dong Hyun, practicing in Seoul, South Korea. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003281; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; south korea; seoul